Subverted and Internal: Portrayals of Home in Women’s Refugee Writings - Martinez del Barrio, Carla (Satura, 2024)
In the essay, I explore the gendered transformations of the concept of home within forced displacement as depicted in literary works by African refugee women. Drawing upon Salman Rushdie’s ideas on home from Imaginary Homelands: Essays and Criticism 1981-1991, this analysis focuses on two narratives: Meron Hadero’s ‘A Down Home Meal for These Difficult Times’ (2022) and Novuyo Rosa Tshuma’s ‘New Lands, New Selves’ (2018). The essay delves into the fluidity and evolution of home as experienced by displaced women, considering home not solely as a physical location but as a construct shaped by memory, imagination, and narrative. Hadero’s text showcases Ethiopian women in New York City, subverting cultural expectations by establishing a culinary business that fosters economic independence and transcultural connections. Meanwhile, Tshuma’s story explores the internalization of home, highlighting the protagonist’s hybrid identity and resilience amid encounters with stereotypes and discrimination. Through these analyses, I unpack how these women redefine and internalize the notion of home amidst displacement, challenging Western stereotypes and emphasizing the need for complex narratives that honor the multiplicity of identities shaped by migration and resilience. The essay underscores the significance of subversion and internalization in redefining home within the context of forced displacement and transcultural experiences.